Long-term, real-world experience of pasireotide dose reduction in patients with acromegaly - Nelma Veronica Marques; Luiz Eduardo Armondi Wildemberg; Monica R Gadelha (Endocrine Connections, 2023)
Pasireotide long-acting release is effective in achieving bioche mical control and reducing tumour volume in patients with acromegaly inadequately controll ed by first-line therapy. As part of a long-term, real-world study at our centre, 20 of 50 patients receiving pasireotide benefited from a reduction in pasireotide dose. Pasi reotide reduced insulin-like growth factor 1 (IGF1) levels to below the upper limit of the normal range, with some patients responding within 1−3 months of treatment (n = 11) and others after ≥4 months (n = 9). Following pasireotide dose reduction, IGF1 levels showed a mild increase but remained within the normal range after a median of 39 months in the early responders and 17 months in the late responders. Glucose and gl ycated haemoglobin levels decreased following dose reduction. Identifying patients who may benefit from a reduction in pasireotide dose warrants further research as it may improve the management of pasireotide-associated hyperglycaemia in susceptible patients. Significance statement: Patients with acromegaly often need medical therapy for extended periods of time, and pasireotide is an effective, long-term trea tment option. However, pasireotide may increase blood glucose levels in some patients, such as those with pre-existing diabetes. In this single-centre study, we show that fo llowing dose reduction of pasireotide over time, patients with acromegaly maintained thei r biochemical response (IGF1 < ULN) and had improved glycaemic control. As such, dose reductions may be an effective, personalised treatment approach for managing some patients receiving long-term pasireotide therapy and could allow patients to achieve early and long-term biochemical control while minimising adverse drug effects.